Perbandingan Kapasitas Pesan pada Steganografi DCT Sekuensial dan Steganografi DCT F5 dengan Penerapan Point Operation Image Enhancement - Dian Hafidh Zulfikar; Agus Harjoko (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2016)
Steganographic  process on the DCT transform is generally done on the value of DCT quantization process results that have a value other than 0, this relates to the distribution of the diversity of pixels in the image. Applying point operation of image enhancement (POIE) in the form of histogram equalization, contrast stretching, brigthening and gamma correction on the image of the reservoir is associated with the image histogram . Test parameters used is the number of bits that can be accommodated message, PSNR and MSE value, and the value of DCT coefficients quantization results.    Based on test results that have to be got several conclusions that capacity steganographic message on DCT sequential greater than the DCT F5 steganography either before or after application of the application POIE, stego image quality on DCT steganography F5 better than the sequential DCT steganography well before the application POIE and after application of POIE, both F5 and steganography steganography DCT DCT sequential equally resistant to manipulation of stego image.